Changsha ware glaze color: Composition, nanostructure, and copper and iron speciation - Yuan, M; Hou, J; Zhang, X; Wood, N; Molera, J; Castillo‐Michel, H; Cotte, M; Pradell, T (Wiley, 2024)
The opacity/transparency, color, and production of designs in Changsha ware, a Tang dynasty Chinese stoneware renowned for its polychromy and pioneering high‐temperature red glaze, are studied by analyzing the composition, micro/nanostructure, and copper/iron speciation. The results shed new light on some of the most debated questions about Changsha ware. In particular, the role of glaze thickness, composition, and firing conditions on the coexistence of transparent and opaque glazes and of oxidized green and reduced red copper designs on the same object, and on the reason for the development of either green or turquoise colors. New data obtained by reproducing a copper red overglaze and underglaze painting with a similar glaze composition and thickness have provided new insights into the origin of the first high‐temperature copper reds and, in the absence of essential knowledge, their discontinuity. This study also contributes to the long debate regarding the use of overglaze versus underglaze painting techniques.